2022
DOI: 10.2147/ijgm.s337321
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Follow-Up of Organizing Pneumonia Associated with Haematological Malignancies

Abstract: Background Organizing pneumonia (OP) is a secondary process in many diseases. Due to its low incidence and indistinct symptoms, there is limited information on OP associated with haematological malignancies. Therefore, the aim of this study was to discuss the characteristics and prognosis of OP associated with haematological malignancies. Methods We observed and analysed pathologically confirmed OP cases associated with haematological malignancies in a hospital record d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In this study, 15 patients were identified as OP and 5 (33%) of them died. The overall mortality of OP in patients with haematologic malignancy varies widely, ranging from 19% to 67%, 8,27–29 but is generally higher than in patients with other underlying diseases 27,30 . The higher mortality in patients with haematologic malignancy is probably multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 15 patients were identified as OP and 5 (33%) of them died. The overall mortality of OP in patients with haematologic malignancy varies widely, ranging from 19% to 67%, 8,27–29 but is generally higher than in patients with other underlying diseases 27,30 . The higher mortality in patients with haematologic malignancy is probably multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Several previous studies attempting to confirm histopathological diagnosis in patients suspected to have invasive pulmonary mould disease have reported the presence of organising pneumonia (OP). [6][7][8] Numerous publications have reported OP to be associated with infectious diseases. [9][10][11][12] However, OP associated with invasive mould disease has only been sporadically reported.…”
Section: Introductionmentioning
confidence: 99%